Electrical Equivalent Model Of Symmetrical Split Ring Resonator Sensor-Based Microwave Technology - Al-Ahnomi, Rammah Ali Hussien; Zakaria, Zahriladha; Mohd Yussof, Zulkalnain; Al-Hegazi, Ammar Abdullah Hussein; Alsariera, Hussein Salameh Mahmoud; Abd Rahman, Norhanani (Wydawnictwo SIGMA-NOT, 2020)
In this paper, a microwave planar sensor based on symmetrical split ring resonator (SSRR) is investigated. This sensor uses ring resonator with slits at 0o and 180o angles as method to realize the harmonic resonant frequency response and then, it integrated with symmetrical split ring for suppressing the undesired harmonic spurious. Compact size, simplicity, cost effective, and ease of fabrication are the main advantage of SSRR sensor. The model of analytical equivalent circuit is proposed and the characteristic of band-pass and band-stop are derived and investigated for the analysed SSRR with/without spurliners filters. The performance and sensitivity of the SSRR sensor is high with an average accuracy between 96% to 98 % at narrow band frequencies. This type of resonators sensors can detect the material properties under their chemical or physical changes which is essential for numerous applications such as quality control, agriculture, bio-sensing, medicine and pharmacy, food industry, and material science.